Rose hip supplementation increases energy expenditure and induces browning of white adipose tissue. Issue 1 (December 2016) - Cavalera, Michele; Axling, Ulrika; Berger, Karin; Holm, Cecilia
Abstract Background Overweight and obesity are widespread chronic disorders defined as excessive fat accumulation, and are major risk factors for several chronic diseases including type 2 diabetes, coronary heart disease, high blood pressure and fatty liver. Changes in lifestyle such as increased physical activity and a healthy diet can be crucial tools for treating obesity. Intake of rose hip, the fruit of several plants belonging to theRosaceae family, has been shown to reduce body fat mass and prevent body weight gain. Thus, the aim of the study was to elucidate potential mechanisms through which rose hip inhibit diet-induced obesity. Methods C57BL/6 J mice were fed a high fat diet with (RH) or without (CTR) rose hip supplementation for three months. In vivo indirect calorimetry was monitored, as well as gene expression and protein levels of different adipose depots. Results Although no differences in energy intake were found compared to the CTR group, RH prevented body weight gain and lowered blood glucose, insulin and cholesterol levels. Indirect calorimetry showed that RH-fed mice have significantly higher EE during the dark phase, despite comparable voluntary activity. Moreover, when challenged with treadmill running, RH-fed mice exhibited higher metabolic rate. Therefore, we hypothesized that RH could stimulate the brown adipose tissue (BAT) thermogenic capacity or may induce browning of the white adipose tissue (WAT). Compared to the CTR group, gene expression and protein levels of some brown and "brite" markers, together with genes able to promote brown adipocyte differentiation and thermogenesis (such asucp1, tbx15, bmp7, andcidea ), as well as phosphorylation of AMPK, was increased in WAT (but not in BAT) of RH-fed mice. Conclusions Taken together these results indicate that dietary rose hip prevents body weight gain by increasing whole body EE and inducing browning of WAT. Thus, it has potential therapeutic implication for treatment of obesity and related metabolic disorders.